A novel one-step synthesis of Ce/Mn/Fe mixed metal oxide nanocomposites for oxidative removal of hydrogen sulfide at room temperature. Issue 43 (5th August 2021) - Gupta, Nishesh Kumar; Bae, Jiyeol; Kim, Kwang Soo
Abstract : In this study, CeO2 /Fe2 O3, CeO2 /Mn2 O3, and CeO2 /Mn2 O3 /Fe2 O3 nanocomposites were synthesized by the calcination of molten salt solutions. Abstract : In this study, CeO2 /Fe2 O3, CeO2 /Mn2 O3, and CeO2 /Mn2 O3 /Fe2 O3 nanocomposites were synthesized by the calcination of molten salt solutions. The microscopic images confirmed polyhedral nanocrystals of 10–20 nm size, clustered to form nanospheres. The elemental mapping confirmed the uniform distribution of transition metal oxides in the CeO2 matrix. The X-ray diffraction analysis confirmed the phase purity of metal oxides in nanocomposites. The surface area of nanocomposites was in the range of 16–21 m 2 g −1 . X-ray photoelectron spectroscopy confirmed 25–28% of Ce 3+ ions in the CeO2 of nanocomposites. These nanocomposites were tested for the removal of hydrogen sulfide gas at room temperature. The maximum adsorption capacity of 28.3 mg g −1 was recorded for CeO2 /Mn2 O3 /Fe2 O3 with 500 ppm of H2 S gas and 0.2 L min −1 of flow rate. The adsorption mechanism probed by X-ray photoelectron spectroscopy showed the presence of sulfate as the only species formed from the oxidation of H2 S, which was further confirmed by ion chromatography. Thus, the study reports room-temperature oxidation of H2 S over mixed metal composites, which were synthesized by a novel one-step approach.